Market Discipline Under Systemic Risk: Evidence from Bank Runs in Emerging Economies - Levy-Yeyati, Eduardo; Martinez Peria, Maria Soledad; Schmukler, Sergio L. (World Bank, Washington, D.C., 2013)
The authors show that systemic risk exerts a significant impact on the behavior of depositors, sometimes overshadowing their responses to standard bank fundamentals. Systemic risk can affect market discipline both regardless of and through bank fundamentals. First, worsening systemic conditions can directly threaten the value of deposits by way of dual agency problems. Second, to the extent that banks are exposed to systemic risk, systemic shocks lead to a future deterioration of fundamentals not captured by their current values. Using data from the recent banking crises in Argentina and Uruguay, the authors show that market discipline is indeed quite robust once systemic risk is factored in. As systemic risk increases, the informational content of past fundamentals declines. These episodes also show how few systemic shocks can trigger a run irrespective of ex-ante fundamentals. Overall, the evidence suggests that in emerging economies, the notion of market discipline needs to account for systemic risk.